POLRMT as a Novel Susceptibility Gene for Cardiotoxicity in Epirubicin Treatment of Breast Cancer Patients - Alejandro Velasco-Ruiz; Rocio Nuñez-Torres; Guillermo Pita; Hans Wildiers; Diether Lambrechts; Sigrid Hatse; Danielle Delombaerde; Thomas Van Brussel; M. Rosario Alonso; Nuria Alvarez; Belen Herraez; Christof Vulsteke; et al. (MDPI AG, 2021)
Anthracyclines are among the most used chemotherapeutic agents in breast cancer (BC). However their use is hampered by anthracycline-induced cardiotoxicity (AIC). The currently known clinical and genetic risk factors do not fully explain the observed inter-individual variability and only have a limited ability to predict which patients are more likely to develop this severe toxicity. To identify novel predictive genes, we conducted a two-stage genome-wide association study in epirubicin-treated BC patients. In the discovery phase, we genotyped over 700,000 single nucleotide variants in a cohort of 227 patients. The most interesting finding was rs62134260, located 4kb upstream of POLRMT (OR = 5.76, P = 2.23 × 10−5). We replicated this association in a validation cohort of 123 patients (P = 0.021). This variant regulates the expression of POLRMT, a gene that encodes a mitochondrial DNA-directed RNA polymerase, responsible for mitochondrial gene expression. Individuals harbouring the risk allele had a decreased expression of POLRMT in heart tissue that may cause an impaired capacity to maintain a healthy mitochondrial population in cardiomyocytes under stressful conditions, as is treatment with epirubicin. This finding suggests a novel molecular mechanism involved in the development of AIC and may improve our ability to predict patients who are at risk.